Verification of the Efficacy of New Insecticide, Diesel (Lufenuron+Emamectin Benzoate) against Onion Thrips (Thrips Tabaci Lindeman) in Bale, south-eastern Ethiopia - Mohammedamin Abdurezake; Guta Eshetu (Open Journal of Plant Science - Peertechz Publications, 2021)
Onion (Allium cepa) is popularly called as "Queen of Kitchen" as it is used as food, salad, spice, condiment and in medicine. Currently, the production is practiced all over the round for its daily uses in food and source of income and for commercial purposes starting from the introduction in the country as planting material from Sudan. However, its productivity is constrained by both biotic and abiotic factors of production. Thrips, thrips tabaci Lindeman (Thysanoptera: Thripidae) is the most limiting factor and causes significant yield loses among biotic factors. In this study, the efficacy of the new insecticide (Diesel (Lufenuron+Emamectin benzoate) was tested with standard check (CORSA (Profenofos 40% + Cypermethrin 4%EC) and unsprayed check included for comparison in three location (Sinana on station, Goba and Aloshe) using a plot size of 10m by 10m for each treatment. Accordingly, the result found that, the new insecticide was effective as of the standard check in controlling the infestation of thrips and reducing the yield losses which contributes in increasing both production and productivity of onion. Therefore, Diesel (Lufenuron+Emamectin benzoate) insecticide can be registered and used as management option for control of onion thrips in Ethiopia.